Comparative Analysis of User Satisfaction of End User Computing Satisfaction, DeLone & McLean and Webqual 4.0 Methods - Wahyu Tedi Prastio; Farikhin; Aris Sugiharto (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to analyze the level of user satisfaction of the SIAP Undip Mobile Application version 2.1.9 using three evaluation methods: End User Computing Satisfaction (EUCS), Delone and McLean, and Webqual 4.0. The study involved 100 Diponegoro University student respondents who used the application. Data was collected through a questionnaire distributed via Google Form and analyzed with SmartPLS 4.0 software to test validity, reliability, and research hypotheses. In this study, there were 11 hypotheses tested with three models. In the EUCS model, one hypothesis is accepted, namely Format has a significant effect on user satisfaction, while the other four hypotheses are rejected. In the Delone and McLean model, two hypotheses were accepted (Information Quality and System Quality) and one hypothesis was rejected (Service Quality). In the Webqual 4.0 model, one hypothesis is accepted (Service Interaction Quality) and two hypotheses are rejected (Information Quality and Usability Quality). The results of this study also provide suggestions for improvement for the development of the SIAP Undip version 2.1.9 application.